Continued impact of COVID-19 pandemic on clinical and translational science early-career researchers. Issue 1 (7th December 2023) - Mayowski, Colleen; Meagher, Emma A.; Althouse, Andrew D.; Patino-Sutton, Cecilia; Thakar, Maya S.; Welch, Julie L.; Rubio, Doris M.; White, Gretchen E.
Abstract: The COVID-19 pandemic had an immediate impact on the lives and work of early-career researchers. We leveraged a cluster-randomized trial and compared survey data collected over two timepoints to explore whether these impacts persisted. Although more than a year had passed, 74% of participants reported that their research was affected in multiple ways in both 2020 and 2021. These data suggest that the effects of the pandemic on early-career researchers may be prolonged. Our findings additionally serve as an impetus to identify and implement solutions to early-career challenges that undoubtedly existed before the pandemic, but which COVID-19 brought into the spotlight.